Early TCR Signaling Sweetens Effector Function through PDHK1. (September 2018) - Weisshaar, Nina; Madi, Alaa; Cui, Guoliang
Abstract : T cells rapidly engage glycolysis upon activation. The signaling pathways through which T cell receptor (TCR) activation initiates glycolysis have been a mystery. A long-awaited answer has been provided by Menk et al ., who show that pyruvate dehydrogenase kinase 1 (PDHK1) is in the center of signaling events linking TCR activation to glycolysis.